Pengaruh Ukuran Perusahaan,Good Corporate Governance Dan Pengungkapan Corporate Social Responsibility Terhadap Nilai Perusahaan (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2013-2015) - Putri, Atikah Evamaya Nur Aini, Drs. Atwal Arifin, M.Si., C.A (2017)
This research aimed to analyze the influence of company size, good corporate governance pervade managerial wnership, institutional ownership, independent commisioners and corporate social responsibility disclosure to firm value in banking company which listed in Indonesian Stock Exchange period 2013-2015. The population used in this study are all banking company which listed in Indonesian Stock Exchange period 2013-2015. The study used purposive sampling method to collect the sample. The number of samples collected as many as 18 companies with 54 data. The collected data were analyzed using data analysis first conducted classical assumption test before hypothesis test. Testing the hypothesis in this study using multiple regression analysis with t-test, f-tets and the coefficient of determination. The results showed that the coefficient of determination obtained a value of 0,169 which means that 16,9% firm value is affected company size, managerial ownership, stitutional ownership, independent commisioners and corporate social responsibility disclosure the balance of 83,1% is influenced by other variables outside the research. Hypotesis test results showed that the company size, institutional ownership and corporate social responsibility disclosure have significant effect on firm value, while the managerial ownership and independent commisioners have not significant effect on firm value.